(untitled) (Innovative professional education, 2024)
The problem of adapting students, especially first-year students, to the college environment is not new, because the further professional career and personal development of the future specialist largely depends on the success of this process. The concept of adaptation can be considered as the process of adapting a student to new conditions, entering a new social environment, learning the norms of such an environment and developing a new model of behavior. The ability of an individual to actively adapt to the conditions of the environment, both physical and social, is defined as adaptability and reflects the correspondence between the goal and the results that must be achieved in the process of obtaining higher education.